ANALISIS WILAYAH KERJA PUSKESMAS DI KOTA BENGKULU TAHUN 2021 - Aqilla Fadia Utari; Ahyuni Ahyuni (JURUSAN GEOGRAFI FIS UNP, 2023)
The aims of this study were (1) to find out how wide the working area of ​​the puskesmas in Bengkulu City is. (2) Knowing the ideal distance for services between health centers in Bengkulu City by utilizing the buffer and network analyst methods. The research method used is descriptive quantitative method by utilizing geographic information systems in the form of buffer analysis techniques and network analyst service areas. The results of this study indicate 1) The area of ​​work with the largest number is the Padang Serai Health Center UPTD with a working area of ​​34,712 km² which includes three working area sub-districts namely Padang Serai Sub-District, Sumber Jaya Sub-District and Teluk Sepang Sub-District. Then the smallest working area is UPTD Anggut Atas with a working area of ​​0.890 km² which includes five working areas namely Anggut Atas Sub-District, Anggut Dalam Sub-District, Kebun Geran Sub-District, Kebun Dahri Sub-District and Pengantungan Sub-District. The working area of ​​the UPTD Puskesmas is spread over 9 sub-districts in Bengkulu City, where in each sub-district there are 2 to 3 UPTD Puskesmas that can reach and serve the entire community in Bengkulu City. fulfilling the ideal service distance of 2 km as many as 13 puskesmas and 7 puskesmas did not meet the ideal service distance. In other words, the Puskesmas in Bengkulu City are sufficient to serve the entire community when viewed from the average number of supporting population of 18,595 people served in each puskesmas. This range can serve up to 9 work areas that can be accommodated by the UPTD in Bengkulu City.Keywords: Health Center, buffer, network analyst, distance, Bengkulu City.